Hubungan Kualitas Tidur dengan Prestasi Belajar Siswa/I Kelas X di SMKN 6 Kota Tangerang - Latifah, Diba; Rochmani, Siti; Faridah, Ida (Pustaka Galeri Mandiri, 2026)
Sleep is a basic human need that plays a crucial role in supporting physiological and cognitive functions, especially during adolescence. Poor sleep quality can affect students’ concentration, memory, and academic performance. To identify and analyze the relationship between sleep quality and the academic performance of 10th-grade students at SMKN 6 Kota Tangerang. Sampling technique using simple random sampling. The sample totaled 163 respondents. Data analysis using the Chi Square correlation test. Based on the study results, good sleep quality was reported by 136 respondents (83.4%), while poor sleep quality was reported by 27 respondents (16.6%). Low academic achievement was found in 33 respondents (20.2%), whereas high academic achievement was observed in 130 respondents (70.8%). The Chi-Square correlation test between sleep quality and academic performance yielded a p-value of 0.002 (<0.05), indicating that the null hypothesis was rejected and that there is a significant relationship between sleep quality and academic performance among 10th-grade students at SMKN 6 Kota Tangerang.